HUBUNGAN ANTARA MOTIVASI DAN MANAJEMEN STRES DENGAN STRES KERJA PADA GURU SMA SANTO YAKOBUS JAKARTA - Maygha Yosianti Putri; Ida Wahyuni; Daru Lestantyo (Jurnal Kesehatan Masyarakat (Undip), 2018)
Job stress is a feeling that workers perceive that affect work productivity of the workers. Job stress is not only experienced by workers in companies, but can also be experienced by educators like teachers. Job stress can be influenced by many factors. This study aims to analyze the correlation of motivation and stress management in teachers at Santo Yakobus High School Jakarta. This study uses a type of quantitative research with Cross Sectional design. This research instrument uses a Hamilton Anxiety Rating Scale questionnaire and a questionnaire about motivation and stress management. Based on the results of research that tested using Chi Square, it was concluded that there was no correlation between age, length of work, work environment, relationships in work, income, appreciation, tribute, incentives, sharing stories, expressing feelings, positive thinking, sports, and recreation with teacher’s job stress. There is a correlation between job demands and time management with teacher’s job stress. Job demands in Santo Yakobus High School Jakarta are quite heavy, so the foundation can consider to provide incentives to teachers so that teachers are more motivated and increase morale. In addition, teachers can also manage their time well to minimize the occurrence of job stress.